4m(m-n)^2+4n(n-m)^3
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 20:28:18
4m(m-n)^2+4n(n-m)^34m(m-n)^2+4n(n-m)^34m(m-n)^2+4n(n-m)^34m(m-n)^2+4n(n-m)^3=4m(n-m)^2+4n(n-m)^3=4(n
4m(m-n)^2+4n(n-m)^3
4m(m-n)^2+4n(n-m)^3
4m(m-n)^2+4n(n-m)^3
4m(m-n)^2+4n(n-m)^3
=4m(n-m)^2+4n(n-m)^3
=4(n-m)^2(m+n(n-m))
=4(n-m)^2(n^2-nm+m)
4m(m-n)^2+4n(n-m)^3
[(m-n)^2*(m-n)^3]^2/(m-n)^4
[(m-n)^2*(m-n)^3]^2/(m-n)^4
(m-n)2(n-m)3(n-m)4化简
已知3m=4n,则m/m+n+n/m-n-m^2/m^2-n^2=
[(m+n)(m-n)-(m-n)²+2n(m-n)]÷4n
(m-2n)(2n+m)-(-3m-4n)(4n-3m)=
(3m-4n)(4n+3m)-(2m-n)(2m+n)
[2(m+n)^5-3(m+n)^4+(-m-n)^3]÷[2(m+n)^3]
计算(m+4n)(m-n)-6(m+2n)(m-3n)
(m+4n)(m-n)-6(m+2n)(m-3n)
(m+4n)(m-n)-6(m+2n)(m-3n),
(m-n)(m^5+m^4n+m^3n^2+m²n^3+mn^4+n^5)
计算4(m+n)^2·(-m-n)^3-(m+n)(-m-n)^4+5(m+n)^5
计算 4(m+n)^2*(-m-n)^3-(m+n)(-m-n)^4+5(m+n)^5 请写出步骤...
计算4(m+n)^2乘(-m-n)^3-(m+n)(-m-n)^4+5(m+n)^5
.4(m+n)^2*(m+n)^3-7(m+n)(m+n)^4+5(m+n)^5=
2(m+n)2-(m+n)+4(m+n)-(m+n)2+3(m+n)2 化简求值